THE EFFECT OF GREEN MARKETING, PRODUCT DESIGN, AND BRAND TRUST ON PURCHASE DECISIONS ON TUPPERWARE PRODUCTS IN PURWOKERTO - Ariyanti, Ayu Rizki; Hidayah, Arini; Astuti, Herni Justiana; Haryanto, Totok; Bagis, Fatmah; Ikhsani, Mastur Mujib (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2020)
This study aims to analyze the influence of partial and simultaneous variables green marketing, product design, and brand trust toward a purchase decision of Tupperware product in Purwokerto. The research type is using a quantitative method. The amount of sample this research is 100 respondents who are divided into 4 sub-district which are North Purwokerto, East Purwokerto, South Purwokerto, and West Purwokerto. The data collection technique used is purposive sampling, while analyzing data instruments this study is validity test, reliability test, classical assumption test, multiple linear regression analysis, and goodness of fit. The analysis result showed that simultaneously of green marketing, product design and brand trust had a significant effect towards purchase decision, besides that in partial green marketing had a positive effect and had not significant towards purchase decision, whereas product design and brand trust had a positive effect and significant toward on purchase decision